2013
DOI: 10.1515/libri-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Data Literacy into Information Literacy Programs: Core Competencies and Contents

Abstract: As STEM areas increasingly rely on pre-existing data, either to validate or extend the scientific body of knowledge, students who have baseline knowledge of how to find, evaluate, and access data will have an advantage. Accordingly, undergraduate STEM curricula is increasingly focused on research-based group projects that develop professional skills, building the professional portfolio needed for early career scientists, technologists, and engineers. This project works to develop new tools to implement basic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(132 citation statements)
references
References 2 publications
1
124
0
7
Order By: Relevance
“…The authors of this study also determined that most researchers in this study thought that offering some type of data literacy was required for their students (Carlson et al, 2013). Other studies have also concluded that academic librarians are well positioned to support data literacy and data competencies (Calzada Prado & Marzal, 2013;Gray, 2004;Schield, 2004;Stephenson & Schifter Caravello, 2007).…”
Section: Literature Reviewmentioning
confidence: 76%
“…The authors of this study also determined that most researchers in this study thought that offering some type of data literacy was required for their students (Carlson et al, 2013). Other studies have also concluded that academic librarians are well positioned to support data literacy and data competencies (Calzada Prado & Marzal, 2013;Gray, 2004;Schield, 2004;Stephenson & Schifter Caravello, 2007).…”
Section: Literature Reviewmentioning
confidence: 76%
“…Five sets of competencies have been proposed in the literature that generally describe skills needed to manage and organize data; apply metadata; and curate data for long-term preservation and re-use (Calzada Prado and Marzal 2013;Carlson et al 2011;Qin and D'ignazio 2010;Schneider 2013;Piorun et al 2012). The competencies developed have been platforms for a variety of learning objectives and educational curricula targeted to a number of educational disciplines (Shorish 2015;Frank and Pharo 2016;Whitmire 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data literacy focuses on the following competencies, as outlined by Prado and Marzal (2013): 1. Understanding what data is, and how it affects society 2.…”
Section: Background Research: Determining Data Literacy Needsmentioning
confidence: 99%